Metamorfosi del trauma e violenza tragica (Altre Modernità, 2022)
In ancient times, many poetic genres and literary artworks include violence and blood. Among them, Attic tragedy is particularly marked by a clear paradox: it may be based on physical or psychological violence, but this is never shown directly on stage. Trauma, on the contrary, from time to time may be told, evoked, relived by main characters and by others. Based on this criterion, we may distinguish among modern adaptations those which deliberately choose to show violence and trauma on stage, in more or less explicit ways, and others which evoke them implicitly and even use them for therapeutic purposes.
Keywords: Aeschylus; Persians; Euripides; Bacchae